God Our Father as a Script of Intimacy for those Suffering Shame - Anderson, Tim L. (Journal of spiritual formation & soul care, 2016)
Feelings of shame are normal when suffering guilt from sin, but the church too often gives congregants a simplistic “shame script,” which paints God only as an angry or disappointed judge and so circumvents a lasting relational intimacy with him. For those who struggle to approach God because of the shame they suffer from past sins and current temptations, recent psychological research provides some insight. I demonstrate: those who agonize over feelings of shame need new “cultural scripts” and “life scripts” by which to flourish, new narratives wherein a healthier view of God, self and community might emerge. The starting point is a proper biblical script of God as our Father, a vision of God the Father that resists one-dimensional notions of divine anger and disappointment. A more robust, intimate and grace-filled concept of God the Father, in other words, provides relief to the sufferers of unhealthy shame.